A Retrospective Study Comparing Ridge Changes in Stone Casts after Ridge Preservation between Allograft and Xenograft when Using Acellular Dermal Matrix as an Occlusive Membrane. - Chen, Li-Fan. (2017)
Abstract: Background: Bovine bone mineral (ABBMX) and freeze-dried bone allograft (FDBA) are popular grafting materials of choice in ridge preservation (RP) procedures. The aim of this retrospective equivalence study was to evaluate and to compare the dimensional changes after RP grafted either with ABBMX or FDBA, as well as the effect on the soft tissue dimensions in stone casts. Methods: Stone casts of twenty-eight patients who received extraction and RP grafted with either ABBMX or FDBA were collected in this investigation with a healing period of 4-6 months. Acellular dermal matrix (ADM) was used as a protective membrane. Pre- and post-RP ridge widths, sectional tissue remodeling at 3-mm and 5-mm subgingivally and changes on the height of the adjacent papilla were recorded. Independent-samples t-test was used to compare baseline valuables, sectional ridge resorption, and the papillary height changes between the groups. Between-group comparisons after the surgery were carried out by one sided 95% confidence intervals for ridge width changes. Intra-group comparisons were performed by the paired t-test. The significance level for rejection of the null hypothesis was set at á = 0.05. Results: At the end of the follow-up period, at the 3-mm subgingival level, there was a reduction in the alveolar ridge width of 5.49±2.17 mm (39.38%) for the FDBA group and of 5.09±2.43 mm (36.46%) for the ABBMX group; whereas at the 5-mm subgingival level, there was a reduction of 3.62±1.70 mm (24.39%) for the FDBA group and of 2.65±1.56 mm (17.26%) for the ABBMX group. All intra-group changes were statistically significant (p<0.0001). Between the groups, a significant difference in tissue remodeling was found at the 5-mm subgingival level on the lingual side (p=0.005). Between the buccal and the lingual sides, a statistically significant difference was revealed at the 3mm subgingival level in the ABBMX group (p=0.03). In all cases, the papillae demonstrated a reduction in height regardless the material used. Conclusions: In spite of the grafting materials used, RP does not predictably preserve the alveolar ridge to its full extent. The between group differences in post-RP ridge dimension if any, is most likely to be within 1.86 mm at the 3-mm subgingival level and 2.02 mm at the 5-mm subgingival level.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Periodontology.; Advisor: Wai Cheung.; Committee: Rory O'Neill, An-I Tsai, and Matthew Finkelman.; Keywords: Medicine, and Dentistry.